Study on the prevention system of rockburst for the entire life cycle of underground coal mines - OUYANG Zhenhua; XU Qianhai; ZHANG Ningbo; ZHANG Tianzi; YI Haiyang; SHI Qingwen; LI Wenshuai; WANG Jiajia (矿业科学学报)
The existing prevention and control of rockbursts in mining mainly focus on the production phase, making it challenging to fundamentally curb rockburst disasters. Based on the concept of lifecycle management, the lifecycle of coal mines can be divided into four stages: exploration, construction, production, and closure. "Source" prevention and control measures are implemented during different stages of the mine to address rockbursts. During the exploration stage, the emphasis is on assessing the rockburst proneness and predicting the risk of rockbursts in the newly developed coal seams. In the construction stage, the focus is on identifying the dynamic tendencies and evaluating the risk of rockbursts considering all minable coal seams, as well as the roof and floor strata. This involves conducting a rockburst identification for the mine, establishing a sound prevention mechanism, improving management systems, determining mine capacity, and implementing rockburst prevention designs. In the production stage, rockburst prevention and control measures are implemented in three stages: pre-mining, during mining, and post-mining. During each stage, specific measures are undertaken to mitigate the risks associated with rockbursts. During the closure stage, safety assessments are conducted regarding the recovery of coal pillars to prevent rockbursts. Special prevention measures are developed based on the assessment results. By implementing these measures throughout the entire lifecycle of the mine, from exploration to closure, it becomes possible to address the issue of rockbursts comprehensively and effectively. This approach ensures that preventive actions are taken at the early stages of mine development and continues to manage and control rockburst risks during the operational phases, ultimately enhancing safety and reducing the impact of rockburst disasters.